Correlação entre necessidade de tratamento auto-reportada e índices normativos de cárie dentária em adolescentes – um estudo de coorte - Santos, Susana Aguiar (2019)
This study aimed to evaluate whether self-perceived treatment needs by adolescents are positively associated with treatment assessed evaluated clinically. A cohort was followed up for six years. The study began in 2012, where 1134 12-year-old adolescents were randomly selected from 20 public schools in the city of Santa Maria, RS. In 2014, a first re-evaluation was performed, obtaining a follow up rate of 68%, corresponding to 771 participants. In 2018, a second re-evaluation of these same adolescents was performed, obtaining a follow up rate of 67,8%, corresponding to 769 participants. The study's outcome corresponded to the correlation between self-perception and normative of the need for dental treatment. Self-perception of the patient was evaluated through the global question "Would you say that the health of your teeth, lips, jaws and mouth is: Excellent, good, regular, bad, poor?" The existence of need for dental treatment according to clinical evaluation was represented by the presence of dental caries (DMF index). The examiners independently performed the clinical evaluations using natural light, periodontal probe and flat mouth mirror in the schools and / or residences of the participants. The methodological protocols, such as the application of questionnaires and clinical exams, were also performed in the three evaluations. In the three times there was correlation between the adolescents' perception and the DMF index. (Spearman correlation coefficient). Adolescents who evaluated their oral health as poor had higher DMF-T mean (p <0.05 Mann-Whitney test). When evaluated separately, decayed and missing teeth also showed significant results, showing that adolescents who evaluated their oral health as poor, had higher mean of carious or lost teeth. When evaluated separately, filled teeth had no statistical relevance in the results, demonstrating that there was no agreement with the adolescents' perception. Adolescent’s oral health self-perception was positively associated with normative dental caries indexes, and this agreement is maintained over time.